2013
DOI: 10.1088/0031-9155/58/10/3075
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo-based model of gold nanoparticle radiosensitization accounting for increased radiobiological effectiveness

Abstract: Radiosensitization using gold nanoparticles (AuNPs) has been shown to vary widely with cell line, irradiation energy, AuNP size, concentration and intracellular localization. We developed a Monte Carlo-based AuNP radiosensitization predictive model (ARP), which takes into account the detailed energy deposition at the nano-scale. This model was compared to experimental cell survival and macroscopic dose enhancement predictions. PC-3 prostate cancer cell survival was characterized after irradiation using a 300 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 49 publications
6
135
0
3
Order By: Relevance
“…Similar results were obtained by Lechtman et al using Monte Carlo simulations. 22 Further measurements focusing on this variation between two radiobiological parameters are currently being undertaken by our group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Lechtman et al using Monte Carlo simulations. 22 Further measurements focusing on this variation between two radiobiological parameters are currently being undertaken by our group.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of x-ray irradiation Li et al (2014) reported a dose enhancement value difference of a factor of 2 between the Penelope-2011 (Salvat et al 2011) and Geant4 code (Agostinelli et al 2003, Allison et al 2006. Moreover, dose distributions around the GNPs have been used in combination with radiobiological models (Lechtman et al 2013, Lin et al 2015, McQuaid et al 2016 in order to calculate biological endpoints such as cell survival. This interest in the nanoscale simulations raises a fundamental question; whether the physical interaction model selection can affect the predicted dose distribution around the GNP.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that loading gold NPs into prostate, skin melanoma, and liver tumors, which are later exposed to irradiation, results in greater dose absorption within the tumor than the surrounding tissues 15, 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%